Responses of hematopoietic cells after ionizing-irradiation in anemic adult medaka (Oryzias latipes). (3rd April 2023) - Nagata, Kento; Ohashi, Keita; Hashimoto, Chika; Sayed, Alaa El-Din Hamid; Yasuda, Takako; Dutta, Bibek; Kajihara, Takayuki; Mitani, Hiroshi; Suzuki, Michiyo; Funayama, Tomoo; Oda, Shoji; Watanabe-Asaka, Tomomi
Abstract: Purpose: Hematopoietic tissues of vertebrates are highly radiation sensitive and the effects of ionizing radiation on the hematopoiesis have been studied in mammals and teleosts for decades. In this study, radiation responses in the kidney, the main hematopoietic organ in teleosts, were investigated in Japanese medaka ( Oryzias latipes ), which has been a model animal and a large body of knowledge has been accumulated in radiation biology. Methods: Kidney, the main hematopoietic tissue of adult medaka fish, was locally irradiated using proton and carbon ion beams irradiation system of Takasaki Ion Accelerator for Advanced Radiation Application (TIARA), QST, and the effects on peripheral blood cells and histology of the kidney were investigated. Results: When only kidneys were locally irradiated with proton or carbon ion beam (15 Gy), the hematopoietic cells in the irradiated kidney and cell density in the peripheral blood decreased 7 days after the irradiation in the same manner as after the whole-body irradiation with γ-rays (15 Gy). These results demonstrate that direct irradiation of the hematopoietic cells in the kidney induced cell death and/or cell cycle arrest and stopped the supply of erythroid cells. Then, the cell density in the peripheral blood recovered to the control level within 4 days and 7 days after the γ-ray and proton beam irradiation (15 Gy), respectively, while the cell density in the peripheral blood did not recover after the carbon ion beam irradiation (15 Gy). The hematopoietic cells in the irradiated kidneys temporarily decreased and recovered to the control level within 21 days after the γ-ray or proton beam irradiation (15 Gy), while it did not recover after the carbon ion beam irradiation (15 Gy). In contrast, the recovery of the cell density in the peripheral blood delayed when anemic medaka were irradiated 1 day after the administration of phenylhydrazine. With and without γ-ray irradiation, a large number of hematopoietic cells was still proliferating in the kidney 7 days after the anemia induction. Conclusions: The results obtained strongly suggest that the hematopoietic stem cells in medaka kidney prioritize to proliferate and increase peripheral blood cells to eliminate anemia, even when they are damaged by high-dose irradiation.